Persepsi Mahasiswa Pendidikan Agama Islam terhadap Praktik Pengalaman Lapangan Berbasis Lesson Study - Evva Aini; Fitriyani, Desy; Setyawan, M. Adin (Prodi Pendidikan Agama Islam, 2024)
This research aims to describe the perceptions of Islamic Religious Education students regarding the implementation of Lesson Study-based Field Experience Practices. This research uses a qualitative approach with a case study method. The research subjects were students of Islamic Religious Education at the State Islamic University of K.H. Abdurrahman Wahid Pekalongan who is currently or has taken the Field Experience Practice course. Data was obtained through interviews, observation and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the research show that Islamic Religious Education students have a positive perception of Lesson Study-based Field Experience Practices. Islamic Religious Education students experience the benefits of lesson study, such as increasing pedagogical, professional, personal and social competencies. However, students also face several obstacles, such as limited time and difficulties in designing collaborative learning.